Efektivitas Penegakan UU ITE terhadap Kasus Penyebaran Konten Palsu: Studi Kasus di Pengadilan Negeri Jakarta - Cahya, Lira; Oktavia , Dina; Putri, Sania (Legal Note, 2026)
The spread of fake content or hoaxes through social media threatens social stability in Indonesia, with the ITE Law serving as the primary cyber law enforcement instrument. This study analyzes the effectiveness of ITE Law enforcement through a case study of Decision No. 203/Pid.Sus/2019/PN Jkt.Sel at the South Jakarta District Court using Soerjono Soekanto's legal effectiveness theory framework. Normative juridical methods were employed with statutory and case approaches examining court decisions and secondary documents from accredited journals. Results indicate repressive effectiveness through Articles 28(1) and (3) with penalties up to 6 years imprisonment, yet hindered by unclear definition of "disturbance" limited by the Constitutional Court. Analysis of five legal effectiveness factors (substance, structure, culture, facilities, and society) reveals primary weaknesses in legal culture and enforcement facilities. Recommendations include revising hoax definitions, strengthening cyber patrol units, and judicial training to balance law enforcement with freedom of expression.